2019
DOI: 10.3390/cancers11091326
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefits of Chemotherapy for Patients with Advanced Pancreatic Cancer in A Clinical Real-World Cohort

Abstract: Clinical outcomes of chemotherapy for patients with advanced pancreatic adenocarcinoma in a real-world setting might differ from outcomes in randomized clinical trials (RCTs). Here we show in a single-institution cohort of 595 patients that median overall survival (OS) of patients who received gemcitabine alone (n = 185; 6.6 months (95% CI; 5.5–7.7)) was the same as in pivotal RCTs. Gemcitabine/capecitabine (n = 60; 10.6 months (95% CI; 7.8–13.3)) and gemcitabine/nab-paclitaxel (n = 66; 9.8 months (95% CI; 7.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…The limited effect on survival on population level probably originates from differences in patient selection compared to clinical trials. Another study [24] including patients with advanced pancreatic cancer from a single institution showed that survival could achieve benefits as shown in randomized clinical trials, but that this differed between treatment regimens. Moreover, the study demonstrated protocol adherence to be one of the explanations for differences between real-world outcomes and results in randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…The limited effect on survival on population level probably originates from differences in patient selection compared to clinical trials. Another study [24] including patients with advanced pancreatic cancer from a single institution showed that survival could achieve benefits as shown in randomized clinical trials, but that this differed between treatment regimens. Moreover, the study demonstrated protocol adherence to be one of the explanations for differences between real-world outcomes and results in randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…They did not find a significant difference to the sequence FOLFIRINOX followed by Gem/NabP and FP/Nal-IRI (mOS 25.5 months) [29]. Furthermore, in the previously mentioned study by Kordes et al patients who received FOLFIRINOX had a shorter median OS (9.9 months, 95% CI; 8.1-11.7) than previously reported [21]. In that respect and in light of no head-to-head prospective comparison trials, there is still no evidence that FOLFIRINOX in the palliative setting is associated with increased survival compared to Gem/NabP.…”
Section: Discussionmentioning
confidence: 75%
“…Our hypothesis is strengthened by other reports. A recent study by Kordes M et al reported that the sequence of gemcitabine-based therapy after 5-FU/oxaliplatin with or without irinotecan was associated with poorer outcomes than a 5-FU-based treatment after a gemcitabine-based doublet therapy [21]. Another study by Caparello and colleagues reports for the subgroup of patients who received Gem/NabP after the failure of first line FOLFIRINOX disappointing results in terms of both activity (RR: 7%; DCR: 23%) and survival (median PFS: 1.95 months; median OS: 5.4 months) [22].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with lower performance status and comorbidity, best supportive care or palliative chemotherapy with milder regimes such as gemcitabine monotherapy remain the only therapeutic options. In these groups of patients, survival is usually limited to around 1-2 [9] and 6 months respectively, the latter which appears similar in randomised controlled trials and real-world populations [7][8][9]11].…”
Section: Background and Rationale {6a}mentioning
confidence: 74%
“…In patients with adequate Eastern Cooperative Oncology Group (ECOG) performance status zero to two and acceptable organ functions, palliative chemotherapy may prolong life and reduce disease related symptomatic burden. For reasonably 'fit' patients treated with chemotherapy combination regimens such as gemcitabine/nab-paclitaxel or FOLFIRINOX, overall survival is usually between 8-11 months [7][8][9][10]. For patients with lower performance status and comorbidity, best supportive care or palliative chemotherapy with milder regimes such as gemcitabine monotherapy remain the only therapeutic options.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%